Linguistic Insights into Eurolect of Institutional Documents Based on the System of Logico-Semantic Relations - Vladislav Hrežo (Language, Culture, Politics)
The present article draws primarily on a text-based approach while aiming attention at researching one genre of EU legal language the judgement in its English language version by employing quantitative and qualitative research methods and serves as a pilot analysis. The analysis is focused on the occurrence of textual Themes used for signalling organization of information and their functioning in the selected text of CJEU judgement based on the Halliday's (1985) theory of information distribution in a text and the system of logico-semantic relations between clauses later adapted by Trklja (2017). On the basis of the data obtained, it follows that the textual Themes denoting different logico-semantic relation types are distributed in the analysed text of EU Judgement unevenly, whereas the most frequent and prevailing type of relation between clauses is represented by lexical items of enhancement denoting causal-conditional relations. The article also provides an overview of previous research of contemporary scholars regarding various aspects of institutional-legal discourse.